3D-printing textiles: multi-stage mechanical characterization of additively manufactured biaxial weaves. (January 2023) - Wirth, M.; Shea, K.; Chen, T.
Graphical abstract: Highlights: This work features the first successful fabrication of 3D-printed textiles that reproduce the topology and structure of traditional woven fabric using the PolyJet process. A large number of weaves are computationally generated within a defined parametric space. These weaves are fabricated and characterized for their mechanical characteristics. We propose a bilinear model to quantify the tensile properties of 3D-printed weaves in yarn direction as well as in diagonal direction. Abstract: 3D printing allows the fabrication of complex microstructures that would traditionally require specialized machinery. In the fabrication of textiles, 3D printing may enable unique yarn structures, greater manufacturing flexibility and facilitate the development of personalized and tunable devices. In literature, 3D printed textiles have not been subjected to a thorough mechanical characterization. In this paper, a generative model of 3D printed biaxial weaves is developed and a parametric study to effectively map the design parameters to the weaves' mechanical properties is performed via a two-stage Design-of-Experiments methodology. The samples are printed with material jetting layer by layer in planar direction and destructively tested in tension to obtain the resulting stress–strain behavior. The stress–strain curves are approximated by a bilinear model characterized predominantly by a transition strain and the major modulus after transition. The transition strain is influenced by the load direction and the weave pattern, while the major modulus is impacted by the load direction, the yarn diameter, the weave pattern and the yarn spacing in descending order. Further evaluation of the fracture behavior shows a mitigation of layer-wise delamination. This result indicates that material jetting can enable the production of arbitrary, quasi-continuous textile structures. The characterization results presented here may pave the way towards the design of textiles with spatially varying mechanical properties.